1997
DOI: 10.1046/j.1365-2958.1997.3731744.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations in Shigella flexneri chromosomal and plasmid‐encoded lipopolysaccharide genes on invasion and serum resistance

Abstract: SummaryThis study shows that both length and distribution of lipopolysaccharide (LPS) are important for Shigella flexneri invasion and virulence. Mutants were generated in the chromosomal LPS synthesis genes rfa, rfb, and rol, and in a plasmid-encoded O-antigen chain-length regulator, cld pHS-2 . LPS analysis showed that mutations in rfb genes and in a candidate rfaL gene either eliminated the entire O-antigen side chains or produced chains of greatly reduced length. Mutation in a previously unidentified gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 35 publications
6
120
1
Order By: Relevance
“…Whilst LPS Oag has previously been shown to shield OM proteins from colicin in E. coli (van der Ley et al, 1986), the impact of Oag chain length against colicins has not been investigated. We propose here that Shigella flexneri regulation of S-type Oag chains is required for conferring resistance to colicin, whilst Shigella flexneri regulation of the VL-type Oag chains is required for conferring resistance to complement (Hong & Payne, 1997), as shown by our serum killing assay (Fig. 5).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whilst LPS Oag has previously been shown to shield OM proteins from colicin in E. coli (van der Ley et al, 1986), the impact of Oag chain length against colicins has not been investigated. We propose here that Shigella flexneri regulation of S-type Oag chains is required for conferring resistance to colicin, whilst Shigella flexneri regulation of the VL-type Oag chains is required for conferring resistance to complement (Hong & Payne, 1997), as shown by our serum killing assay (Fig. 5).…”
Section: Discussionmentioning
confidence: 89%
“…In Shigella flexneri, S-type Oag chains have been shown to contribute to IcsA-mediated actin-based motility and affect virulence (Van Den Bosch et al, 1997), whilst loss of the VL-type Oag chains in Shigella flexneri has been shown to enhance bacterial sensitivity to complement (Hong & Payne, 1997). In Pseudomonas aeruginosa, absence of LPS with long (L)-type Oag chains resulted in greater sensitivity to complement killing and reduced virulence in mice (Kintz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…S. flexneri LPS O-antigen is a virulence factor whose chain length affects both serum resistance and the function of surface virulence factors; a role for LPS in cell invasion has been reported (11,(44)(45)(46). S. flexneri infection has also been blocked by both the addition of free LPS and treatment with anti-LPS antibodies (11,14,21).…”
Section: Discussionmentioning
confidence: 96%
“…Regulation of surface polysaccharide length is an important adaptation that leads to optimal survival and virulence of pathogens [6][7][8]. During LPS Oag biosynthesis, Wzz proteins control Oag modal length distribution through two proposed mechanisms: as a molecular timer of Oag polymerization [9] or in an organizational manner to determine the crucial ratio of the polymerase Wzy to the Oag ligase WaaL [10].…”
Section: Wzy-dependent Polysaccharide Biosynthesismentioning
confidence: 99%